Chitosan immobilised granular FeOOH-MnxOy bimetal-oxides nanocomposite for the adsorptive removal of lead from water. Issue 2 (April 2022) - Naga Jyothi, M.S.V.; Harafan, Afrah; Sen Gupta, Soujit; Neethu, N.; Singhal, Gaurav; Ramaiah, B.J.; Maliyekkal, Shihabudheen M.
Abstract: Mixed metal-oxides are an important class of materials studied for the adsorptive removal of contaminants in water. However, the lack of affordable and versatile immobilisation techniques limits its large-scale deployment in water purification. The present work describes the use of protonated chitosan as a template and reinforcing agent to fabricate FeOOH-Mnx Oy bimetal-oxide granules formed via complexation of metal-oxides with hydroxyl and amine groups in chitosan. The synthesis procedure also enables the modulation of nanocomposite into granules of different shapes and sizes. XRD and XPS analyses confirm the existence of MnO, Mn2 O3, MnO2, and FeOOH phases in the composite. The granules showed excellent affinity to scavenge the model pollutant, Pb 2+, through inner-sphere complexation with an estimated Sips isotherm capacity of 108.12 mg/g. The chemical stability analysis of the composite showed that the leaching of Fe and Mn from the composite is pH, contact time, and temperature dependent. The background ions can also affect the chemical stability of the composite. However, Fe and Mn leaching were well within the permissible limit under typical groundwater pH and temperature. There is no significant effect on Pb 2+ intake by competing ions such as Cl -, NO3 -, HCO3 -, Ca 2+, Fe 2+, and Mn 2+ . In short, the improved adsorption capacity, the ability to form hydraulically stable granules, and ease of synthesis make the composite a practical adsorbent for removing heavy metal ions in water. Graphical Abstract: ga1 Highlights: Less energy-intensive and versatile approach for synthesis and granulation of bimetal-oxides nanocomposite. Hydraulically and chemically stable bimetal-oxides granules with tunable size and shape. A granular FeOOH-MnxOy composite with a Pb 2+ adsorption capacity of 108.12 mg/g. Studied the effect of water quality parameters on the chemical stability of FeMnG.